Infratemporal fossa abscess with leptospirosis resembling stroke - Ealumalai, Schandtinie; Lo, Ren Hui; Tang, Ing Ping; M. Bohari , Nursyahirah Sheila Salinah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Infratemporal fossa (ITF) abscess is the formation of abscess in the deep space bounded above by the greater wing of sphenoid and part of temporal bone, medially by later pterygoid of the sphenoid and anteriorly by the posterior surface of the maxilla. We present a rare case of leptospirosis abscess in infratemporal fossa that resembles stroke. Seventy-four-year-old years old gentleman with hypertension presented with 4 days history of left temporal painful swelling. It is associated with fever and reduced oral intake. He started slurring of speech and right upper limb weakness on the day of presentation. On examination, there was a 3×3 cm firm, warm, painful swelling at left temporal region. There was no gag reflex and the patient had right upper limb weakness (3/5). Leptospirosis IgM was positive. CECT brain showed infratemporal fossa collection. Incision and drainage were done with incision made over left temporal swelling guiding to infratemporal fossa. The patient was treated with intravenous ceftriaxone for 10 days and wound dressings. 2 days post operative, all positive neurological signs recovered. ITF abscess with leptospirosis is rare and can have various atypical presentations. Doctors much always remember such possibilities to prevent delay and mismanagement.